Endoscopic Balloon Dilation of Esophageal Strictures in 9 Horses. (25th June 2015) - Prutton, J.S.W.; Marks, S.L.; Aleman, M.
<x xml:space="preserve">Abstract</x> Background Medical treatment of esophageal strictures in horses is limited and the use of balloon dilatation is described in few cases. Long‐term follow up after balloon dilatation and the use of intralesional corticosteroids has not been evaluated. Objectives To describe the use of endoscopic guided, esophageal balloon dilatation in horses for cervical and thoracic esophageal strictures and administration of intralesional corticosteroids at the time of dilatation. Animals Nine horses from the hospital population with benign esophageal strictures. Methods Retrospective study: Medical records were reviewed from horses presented to the William R. Pritchard, Veterinary Medical Teaching Hospital at UC Davis from 2002 to 2013. Records were searched using the key words: equine, horse, balloon dilatation, bougienage, and esophageal stricture. Results Nine horses with esophageal strictures were treated with esophageal balloon dilatation. Five horses survived (survival at writing ranged from 2 to 11 years after discharge) and all nonsurvivors were <1 year of age and presented with concurrent problems or developed complications including megaesophagus, unresolved esophageal obstruction requiring esophagostomy, or severe aspiration pneumonia. Four horses were treated with intralesional corticosteroids with no adverse effects noted in the survivors (n = 3). Four horses available for long‐term follow up were alive at 2, 5, 6, and 11 years after presentation and 3 of these horses were being fed a hay‐based diet. Conclusions Resolution of esophageal strictures in the horse can be performed successfully, safely, and under standing sedation using balloon dilatation. Intralesional corticosteroids might reduce the incidence of recurrent strictures.